Evaluation of preoperative carbohydrate loading compared to preoperative fasting for enhanced recovery after elective gynecological surgeries - Venkatappa, Shalini; Suri, Vanita; Jain, Vanita; Arora, Aashima; Jain, Kajal; Malhotra, Sunita; Sachdeva, Naresh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: This study aimed to evaluate the impact of preoperative carbohydrate loading on insulin resistance and clinical outcomes in patients undergoing elective gynecological surgeries. Methods: A single-center, parallel-group, randomized controlled study was conducted at the Post Graduate Institute of Medical Education and Research, Chandigarh, India. Thirty-nine patients were randomized into two groups: the carbohydrate loading group (CHO, n=20) received 600 ml of a carbohydrate-rich drink the day before surgery and 200 ml two hours before surgery; the control group (CO, n=19) fasted overnight. Results: Baseline serum insulin, blood glucose, and insulin resistance levels were similar between the groups. Two hours before surgery, the CO group had significantly higher serum insulin levels (7.5±5.6 IU/ml) compared to the CHO group (4.5±2.9 IU/ml) (t=2.08, p=0.04). Insulin resistance was also higher in the CO group (1.9±1.6) compared to the CHO group (0.9±0.6) (t=2.40, p=0.02). Seventy-five percent of the CHO group regained bowel sounds within 24 hours post-surgery, compared to seventy-three percent of the CO group, who achieved bowel sounds after 24 hours (χ²=9.24, p=0.02). No significant differences were observed in postoperative mobilization, urinary catheter removal, fever, nausea, vomiting, length of hospital stay, or surgical site infections. Conclusions: Preoperative carbohydrate loading reduces insulin resistance and facilitates faster bowel recovery without increasing postoperative complications in elective gynecological surgery.